Reflection type wavelength conversion device and preparation method thereof
By adopting a multi-layer phosphor layer and a thermally conductive reflective layer structure in the reflective wavelength conversion device, the problem of insufficient thermal interface and bonding strength between the layers in the existing device is solved, and efficient wavelength conversion is achieved. Heat dissipation effect and improved reliability.
Patent Information
- Application Number
- CN202411869053.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing reflective wavelength conversion devices have obvious thermal interfaces and insufficient bonding strength between layers, resulting in poor heat dissipation effect, increased risk of heat quenching, and may even lead to device damage.
Design a reflective wavelength conversion device, adopting a multi-layer phosphor layer and a thermally conductive reflective layer structure, wherein the fluorescent layer is obtained by sintering of phosphor powder, glass powder and scattering particles, and the thermally conductive reflective layer includes a porous alumina layer, alumina-nitriding The aluminum transition layer and the aluminum nitride layer, the porous tera oxide layer, are arranged close to the fluorescent layer to improve reflectivity and bonding strength.
The wavelength conversion efficiency, extreme blue light resistance, heat dissipation effect and reliability of the wavelength conversion device are improved, the interface thermal resistance is reduced, and the bonding strength between the fluorescent layer and the thermally conductive reflective layer is enhanced.
Smart Images

Figure CN119427849A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wavelength conversion materials and devices thereof, and more specifically, to a reflective wavelength conversion device and a preparation method thereof. Background Art
[0002] Commonly used reflective wavelength conversion devices in the field of laser lighting display include organic silicone color wheel luminescence scheme and inorganic glass color wheel luminescence scheme. The organic silicone color wheel luminescence scheme is mainly used in power levels of 300w and below, such as laser TVs and laser micro-projectors; while the inorganic glass color wheel luminescence scheme is mainly used in power levels of 500w and above, such as high-power laser engineering projectors, laser theater projection light sources, high-power laser searchlights, laser beam lights and other scenes. The conventional structural design of the above organic silicone or inorganic glass wavelength conversion device is an upper fluorescent wavelength conversion layer, a lower fluorescent reflection layer, and a heat dissipation substrate at the bottom. In the above design, the thickness of the wavelength conversion layer and the fluorescent reflection layer is basically in the range of 100μm and above. At this thickness, the wavelength conversion layer and the fluorescent reflection layer are formed separately between the layers, and there is an obvious thermal interface between the two, forming an interface thermal resistance. Furthermore, since the packaging materials of the wavelength conversion layer and the fluorescent reflection layer are different, and the bonding area between the fluorescent reflection layer and the heat dissipation substrate is also limited, the bonding strength between the two layers and between the fluorescent reflection layer and the heat dissipation substrate is insufficient, resulting in increased thermal resistance between the layer interfaces, causing poor heat dissipation of the wavelength conversion device and an increased risk of thermal quenching of the wavelength conversion layer. Even more so, if the fluorescent reflection layer and the heat dissipation substrate are not firmly bonded, in severe cases, the fluorescent reflection layer may fall off from the surface of the heat dissipation substrate together with the wavelength conversion layer when the color wheel device rotates, causing damage to the device. Summary of the invention
[0003] The present invention aims to overcome at least one defect of the above-mentioned prior art and provide a reflective wavelength conversion device, which has high wavelength conversion efficiency, high resistance to extreme blue light power, good heat dissipation effect and good reliability.
[0004] Another object of the present invention is to provide a method for preparing the reflective wavelength conversion device.
[0005] The technical solution adopted by the present invention is:
[0006] A reflective wavelength conversion device comprises a fluorescent layer and a heat-conducting reflective layer arranged below the fluorescent layer, wherein the fluorescent layer is obtained by sintering fluorescent powder, glass powder and scattering particles, the fluorescent layer comprises n fluorescent powder layers, the first fluorescent powder layer is close to the thermally conductive reflective layer, the outermost layer away from the thermally conductive reflective layer is the nth fluorescent powder layer, 2≤n≤5, the fluorescent powder content in the first fluorescent powder layer to the nth fluorescent powder layer increases layer by layer, and the scattering particle content decreases layer by layer, the heat-conducting reflective layer comprises a porous aluminum oxide layer, an aluminum oxide-aluminum nitride transition layer and an aluminum nitride layer stacked in sequence, and the porous aluminum oxide layer is arranged close to the fluorescent layer.
[0007] The reflective wavelength conversion device described in the present application has specially designed the structures of the fluorescent layer and the thermal conductive reflective layer, wherein the fluorescent layer includes multiple layers of fluorescent powder layers, each layer of which has different contents of fluorescent powder and scattering particles. The fluorescent powder layer close to the thermal conductive reflective layer has less fluorescent powder and more scattering particles, which together with the porous alumina layer are mainly responsible for reflecting fluorescence. The fluorescent powder layer away from the thermal conductive reflective layer has more fluorescent powder and less scattering particles, which is mainly responsible for providing most of the fluorescence. Each layer of fluorescent powder layer uses the same type of components, so that there is no obvious interface between the prepared fluorescent layers. The thermal conductive reflective layer is designed to be a porous aluminum oxide layer, an aluminum oxide-aluminum nitride transition layer and an aluminum nitride layer structure stacked in sequence, and the porous aluminum oxide layer is arranged close to the fluorescent layer, so that the thermal conductive reflective layer has excellent heat dissipation performance, high tolerance performance and strong bonding performance. The reason is that the refractive index difference between the air inside the porous aluminum oxide pores and the aluminum oxide can make the porous aluminum oxide layer have a very high reflectivity (the refractive index of the porous medium is 1, the refractive index of aluminum oxide is 1.75, and the refractive index difference between the two is 0.75, which has a strong scattering effect on fluorescence, so that the porous aluminum oxide layer has a very high reflectivity). Therefore, the porous aluminum oxide layer close to the fluorescent layer plays a fluorescent reflection role, which can replace the traditional diffuse reflection layer solution using glass powder plus diffuse reflection particles. In addition, since there are many holes in the contact interface between the porous alumina and the fluorescent layer, the glass powder in the fluorescent layer will melt and penetrate into the porous alumina layer to a certain depth during the sintering stage, increasing the bonding contact area between the fluorescent layer and the porous alumina layer, forming a strong bond between the two, significantly improving the bonding strength, and reducing the interface thermal resistance between the fluorescent layer and the reflective layer. In addition, the alumina layer has a higher thermal conductivity than the traditional diffuse reflection layer composed of glass powder and diffuse reflection particles, so that the wavelength conversion device can withstand high laser power, and the fluorescent layer has better thermal quenching resistance; the aluminum nitride layer as a thermal conductive layer has a very high thermal conductivity, good thermal conductivity, and can quickly conduct heat; the aluminum oxide-aluminum nitride transition layer is a complex phase structure of aluminum oxide phase and aluminum nitride phase, which has good bonding strength with aluminum oxide and aluminum nitride, plays a bonding modification role, and improves the thermal stability of the wavelength conversion device. Therefore, the thermal conductive reflective layer has good overall heat dissipation effect, high laser power resistance, and good thermal stability.
[0008] In one embodiment, the mass ratio of the phosphor to the glass powder in the phosphor layer is (0.1-2):1, and the mass ratio of the scattering particles to the glass powder is (0.1-1):1.
[0009] In one embodiment, the mass ratio of phosphor to glass powder in the first phosphor layer of the phosphor layer is (0.1-0.3):1, and the mass ratio of scattering particles to glass powder is (0.7-1):1; the mass ratio of phosphor to glass powder in the nth phosphor layer of the phosphor layer is (1-2):1, and the mass ratio of scattering particles to glass powder is (0.1-0.2):1.
[0010] In one embodiment, the scattering particles are one or a combination of aluminum oxide, titanium oxide, zirconium oxide, magnesium oxide, zinc oxide, and lithopone, and the particle size is 20-400 nm.
[0011] In one embodiment, the softening temperature of the glass powder is 500-700° C., the glass powder is a Zn / B / Si / O system, an Al / Zn / B / O system or a B / Si / O system, and the particle size is 1-6 μm.
[0012] In one embodiment, the porous aluminum oxide layer and the aluminum oxide-aluminum nitride transition layer of the thermal reflective layer are obtained by oxidation of aluminum nitride. The thermal reflective layer can be formed by thermal oxidation of aluminum nitride. The porous aluminum oxide layer, the aluminum oxide-aluminum nitride transition layer and the aluminum nitride layer of the thermal reflective layer are integrated, with good adhesion and low interface thermal resistance. The porous aluminum oxide layer is obtained by oxidation of aluminum nitride, so that the porous aluminum oxide layer still retains a crystal structure, and the wavelength conversion device can withstand higher laser power.
[0013] In one embodiment, the pores of the porous alumina layer have a pore size of 100-400 nm.
[0014] In one embodiment, the thickness of the porous aluminum oxide layer is 50 to 70 μm, and the thickness of the aluminum oxide-aluminum nitride transition layer is 5 to 15 μm.
[0015] In one embodiment, the thickness of the fluorescent layer is 80-140 μm, and the thickness of the thermal conductive reflective layer is 0.5-1 mm.
[0016] The method for preparing the reflective wavelength conversion device comprises the following steps:
[0017] (1) Oxidation treatment of the heat sink substrate: The aluminum nitride substrate is placed in an oxygen atmosphere, the oxygen partial pressure is controlled to be 0.06-0.1 MPa, the heat treatment temperature is 800-900°C, and the temperature is kept for 30-60 minutes to obtain an oxidized aluminum nitride substrate having a porous aluminum oxide layer on the surface and an aluminum oxide-aluminum nitride transition layer in the middle;
[0018] (2) grinding and polishing the oxidized aluminum nitride substrate: one side of the oxidized aluminum nitride substrate is not processed in any way and serves as a fluorescent reflection surface, and the remaining surface of the oxidized aluminum nitride substrate is ground and polished to expose the aluminum nitride layer;
[0019] (3) preparing fluorescent slurry: preparing fluorescent slurries of different layers according to the ratio of different fluorescent powder layers: adding glass powder, scattering particles and fluorescent powder into a mortar according to the ratio, adding organic solvent, grinding and stirring, and then planetary vacuum stirring to evenly disperse and remove bubbles of each component, to obtain fluorescent slurries of the first fluorescent powder layer,,,,, and the nth fluorescent powder layer respectively;
[0020] (4) Laminating the first phosphor layer fluorescent slurry on the aluminum nitride substrate: Printing the first phosphor layer fluorescent slurry on the fluorescent reflection surface of the aluminum nitride substrate by screen printing to obtain a first phosphor layer wet film;
[0021] (5) Pre-drying the wet film of the first phosphor layer: drying the wet film of the first phosphor layer in an oven, controlling the pre-drying temperature at 100-120° C., and keeping the temperature for 30-60 min to obtain a dry film of the first phosphor layer;
[0022] (6) Laminating and drying the remaining layers of fluorescent slurry: coating and drying the remaining layers of fluorescent slurry in sequence according to the methods of steps (4) and (5);
[0023] (7) Sintering to obtain a finished product: In an air atmosphere, the aluminum nitride substrate with an n-layer phosphor layer attached to the surface prepared in step (6) is sintered in a high-temperature sintering furnace, the peak sintering temperature is controlled at 750-850° C., and the temperature is kept at 30-90 minutes to obtain a wavelength conversion device.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: the present application adopts a multi-layer design for both the fluorescent layer and the thermal conductive reflective layer, wherein the content of the fluorescent powder and the scattering particles in the fluorescent layer is designed in a gradient manner, wherein the content of the fluorescent powder in the fluorescent powder layer close to the thermal conductive reflective layer is less and the content of the scattering particles is more, and the fluorescent powder layer is mainly responsible for reflecting the fluorescent powder; the content of the fluorescent powder in the fluorescent powder layer away from the thermal conductive reflective layer is more and the content of the scattering particles is less, and the fluorescent powder layer is responsible for providing most of the fluorescent powder; each layer of the fluorescent powder layer adopts the same type of components, so that there is no obvious interface between the prepared fluorescent layers; the thermal conductive reflective layer includes a porous aluminum oxide layer, an aluminum oxide-aluminum nitride transition layer and an aluminum nitride layer structure stacked in sequence, wherein the refractive index between the air inside the porous aluminum oxide layer and the aluminum oxide is The difference can make the porous alumina layer have a very high reflectivity, and because there are many holes in the contact interface between the porous alumina and the fluorescent layer, the glass powder in the fluorescent layer will melt and penetrate into the porous alumina layer to a certain depth during the sintering stage, increasing the bonding contact area between the fluorescent layer and the porous alumina layer, forming a strong bond between the two, and significantly improving the bonding strength, reducing the interface thermal resistance between the fluorescent layer and the reflective layer; the aluminum nitride layer as a thermal conductive layer has a very high thermal conductivity coefficient and good thermal conductivity, and can quickly conduct heat; the aluminum oxide-aluminum nitride transition layer is a complex phase structure of aluminum oxide phase and aluminum nitride phase, and it has good bonding strength with aluminum oxide and aluminum nitride, plays a bonding modification role, and improves the thermal stability of the wavelength conversion device. The reflective wavelength conversion device has high wavelength conversion efficiency, high resistance to extreme blue light power, good heat dissipation effect, and good reliability. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a simplified schematic diagram of the structure of the reflective wavelength conversion device of Example 1. Figure 2 This is a schematic diagram of the structure of the reflective wavelength conversion device of Example 2. Figure 3 This is a schematic diagram of the structure of the reflective wavelength conversion device of Example 3. Figure 4 This is a schematic diagram of the structure of the reflective wavelength conversion device of Example 4. Figure 5 This is a schematic diagram of the structure of the reflective wavelength conversion device of Example 5. Figure 6 This is a simplified schematic diagram of the structure of the reflective wavelength conversion device of Example 6. Figure 7 This is a schematic diagram of the structure of the reflective wavelength conversion device of comparative example 1. Figure 8 This is a schematic diagram of the structure of the reflective wavelength conversion device of comparative example 2. Explanation of the reference numerals: 1. phosphor layer; 11. first phosphor layer; 12. second phosphor layer; 13. third phosphor layer; 14. fourth phosphor layer; 15. fifth phosphor layer; 2. thermal conductive reflective layer; 21. aluminum nitride layer; 22. aluminum oxide-aluminum nitride transition layer; 23. porous aluminum oxide layer. DETAILED DESCRIPTION
[0025] In order to make the application purpose, technical solution and beneficial technical effect of the present application clearer, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.
[0026] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0027] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and the “multiple” in “one or more” means more than two.
[0028] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0029] During the research process, the inventors found that for the common reflective wavelength conversion devices on the market, when the fluorescent layer and the diffuse reflection layer are bonded, due to the different configurations and functions of the layers and the thicknesses of all the layers being above 100um, there are obvious interfaces between the layers, resulting in problems with the bonding strength between the layers.
[0030] This application is proposed based on the discovery and research of the above-mentioned problems.
[0031] In one embodiment of the present application, the first aspect of the present application provides a reflective wavelength conversion device, comprising a fluorescent layer 1 and a thermally conductive reflective layer 2 arranged below the fluorescent layer 1, the fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles, the fluorescent layer comprises n fluorescent powder layers, the first fluorescent powder layer 11 is close to the thermally conductive reflective layer 2, and the outermost layer away from the thermally conductive reflective layer is the nth fluorescent powder layer, 2≤n≤5, the fluorescent powder content in the first fluorescent powder layer 11 to the nth fluorescent powder layer increases layer by layer, and the scattering particle content decreases layer by layer, the thermally conductive reflective layer 2 comprises a porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22 and an aluminum nitride layer 21 stacked in sequence, and the porous aluminum oxide layer 23 is arranged close to the fluorescent layer 1.
[0032] By gradient designing the content of the phosphor and scattering particles in different phosphor layers of the phosphor layer 1, the phosphor layer close to the thermal conductive reflective layer 2 has less phosphor content and more scattering particles, which are mainly responsible for reflecting fluorescence together with the porous aluminum oxide layer 23. The phosphor layer away from the thermal conductive reflective layer 2 has more phosphor content and less scattering particles, which are mainly responsible for providing most of the fluorescence. Each phosphor layer uses the same type of components, so that there is no obvious interface between the phosphor layers of the prepared phosphor layer 1.
[0033] The thermal conductive reflective layer 2 comprises a stacked porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22 and an aluminum nitride layer 21, and the porous aluminum oxide layer 23 is arranged close to the fluorescent layer 1. The porous aluminum oxide layer 23 close to the fluorescent layer 1 can replace the traditional diffuse reflection layer using glass powder plus diffuse reflection particles to play a fluorescent reflection role. The refractive index difference between the air inside the porous aluminum oxide pores and the aluminum oxide is large, which can make the porous aluminum oxide layer 23 have a very high reflectivity (the refractive index of the porous medium is 1, the refractive index of aluminum oxide is 1.75, and the refractive index difference between the two is 0.75, which is relatively large, and can have a strong scattering effect on the fluorescence, so that the porous aluminum oxide layer 23 has a very high reflectivity). In addition, since there are many holes at the contact interface between the porous aluminum oxide layer 23 and the fluorescent layer 1, the glass powder in the fluorescent layer 1 melts during the sintering stage and penetrates into the porous aluminum oxide layer 23 to a certain depth, increasing the bonding contact area between the fluorescent layer 1 and the porous aluminum oxide layer 23, forming a strong bond between the two, significantly improving the bonding strength, and reducing the interface thermal resistance between the fluorescent layer 1 and the thermal conductive reflective layer 2. Aluminum oxide has a higher thermal conductivity, which can make the wavelength conversion device withstand high laser power, and the fluorescent layer 1 has better thermal quenching resistance; the aluminum nitride layer 21 is a thermal conductive layer, and its thermal conductivity is very high, and the thermal conductivity effect is good, and it can quickly conduct heat. The aluminum oxide-aluminum nitride transition layer 22 is a composite structure of aluminum oxide phase and aluminum nitride phase, and it has good bonding strength with aluminum oxide and aluminum nitride, plays a bonding modification role, and improves the thermal stability of the wavelength conversion device. Through the multi-layer structure design of the fluorescent layer 1 and the multi-layer structure design of the heat-conducting reflective layer 2, the wavelength conversion device has high wavelength conversion efficiency, high resistance to extreme blue light power, good heat dissipation effect and good reliability.
[0034] Furthermore, considering the cost and effect of the wavelength conversion device, n is preferably 2≤n≤4.
[0035] In any embodiment, the mass ratio of the phosphor to the glass powder in the phosphor layer 1 is (0.1-2): 1, and the mass ratio of the scattering particles to the glass powder is (0.1-1): 1. More specifically, the mass ratio of the phosphor to the glass powder in the first phosphor layer 11 of the phosphor layer 1 is (0.1-0.3): 1, for example, 0.1: 1, 0.2: 1, 0.3: 1, etc.; the mass ratio of the scattering particles to the glass powder is (0.7-1): 1, for example, 0.7: 1, 0.8: 1, 0.9: 1, 1: 1, etc. The mass ratio of phosphor to glass powder in the nth phosphor layer of the phosphor layer 1 is (1-2):1, for example, it can be 1:1, 1.5:1, 2:1, etc., and is preferably (1.5-2:1); the mass ratio of scattering particles to glass powder is (0.1-0.2):1, for example, it can be 0.1:1, 0.15:1, 0.2:1, and is preferably (0.15-0.2:1).
[0036] In any embodiment, the scattering particles are one or a combination of aluminum oxide, titanium oxide, zirconium oxide, magnesium oxide, zinc oxide, and lithopone, and the particle size is 20-400 nm. These scattering particles have good scattering performance and light transmittance. Further preferably, the particle size of the scattering particles is 50-100 nm.
[0037] In any embodiment, the softening temperature of the glass powder is 500-700° C., the glass powder is a Zn / B / Si / O system, an Al / Zn / B / O system or a B / Si / O system, and the particle size is 1-6 μm.
[0038] Furthermore, the porous aluminum oxide layer 23 and the aluminum oxide-aluminum nitride transition layer 22 of the thermal conductive reflective layer 2 are obtained by oxidation of aluminum nitride. In this way, the thermal conductive reflective layer 2 can be formed by thermal oxidation of aluminum nitride, and the porous aluminum oxide layer 23, the aluminum oxide-aluminum nitride transition layer 22 and the aluminum nitride layer 21 of the thermal conductive reflective layer 2 are integrated, with good adhesion and low interface thermal resistance.
[0039] More specifically, the pores of the porous aluminum oxide layer 23 have a pore size of 100-400 nm. Experiments have shown that when the pore size of the porous aluminum oxide layer 23 is 100-400 nm, the reflection effect is optimal.
[0040] In any embodiment, the thickness of the porous aluminum oxide layer 23 is 50-70 μm, and the thickness of the aluminum oxide-aluminum nitride transition layer 22 is 5-15 μm. The porous aluminum oxide layer 23 described in the present application is obtained by oxidation of aluminum nitride, and the aluminum oxide-aluminum nitride transition layer 22 is obtained by incomplete oxidation of aluminum nitride. The thickness of the porous aluminum oxide layer 23 and the aluminum oxide-aluminum nitride transition layer 22 can be controlled by controlling the oxygen partial pressure, the sintering temperature and the holding time.
[0041] In any embodiment, the thickness of the fluorescent layer 1 is 80-140 μm, for example, 80 μm, 100 μm, 120 μm, 140 μm, etc., preferably 80-90 μm, and the thickness of the thermal conductive reflective layer 2 is 0.5-1 mm, for example, 0.5 mm, 0.8 mm, 1 mm, etc.
[0042] The method for preparing the reflective wavelength conversion device comprises the following steps:
[0043] (1) Oxidation treatment of heat sink substrate: The aluminum nitride substrate is placed in an oxygen atmosphere, the oxygen partial pressure is controlled to be 0.06-0.1Mpa, the heat treatment temperature is 800-900℃, and the temperature is kept for 30-60min to obtain an oxidized aluminum nitride substrate with a porous aluminum oxide layer 23 on the surface and an aluminum oxide-aluminum nitride transition layer 22 in the middle. The aluminum nitride on the surface of the aluminum nitride substrate reacts with oxygen to generate a porous aluminum oxide layer. In addition, the oxidation reaction of aluminum nitride with oxygen is carried out gradually from the outside of the aluminum nitride to the inside. The aluminum nitride in the slightly inner layer does not have time to capture oxygen, thereby forming a transition layer between aluminum oxide and aluminum nitride; and the aluminum nitride further inside has almost no contact with oxygen, and the oxidation reaction cannot proceed, and it is still made of aluminum nitride.
[0044] (2) Grinding and polishing the oxidized aluminum nitride substrate: One side of the oxidized aluminum nitride substrate is not processed and used as a fluorescent reflection surface, and the remaining surface of the oxidized aluminum nitride substrate is ground and polished to expose the aluminum nitride layer 21. The thermal conductivity of aluminum nitride is better than that of the porous aluminum oxide layer on the surface. The aluminum oxide layer and the transition layer between aluminum nitride and aluminum oxide are ground off to expose the aluminum nitride layer 23, so that the thermal conductive reflective layer 2 can maintain high thermal conductivity.
[0045] (3) preparing fluorescent slurry: preparing fluorescent slurries of different layers according to the ratio of different fluorescent powder layers: adding glass powder, scattering particles and fluorescent powder into a mortar according to the ratio, adding organic solvent (the organic solvent can be pine alcohol, methyl acetate, ethyl acetate, etc.), grinding and stirring, and then planetary vacuum stirring to evenly disperse and remove bubbles of each component, to obtain fluorescent slurries of the first fluorescent powder layer,,,,, and the nth fluorescent powder layer respectively;
[0046] (4) Laminating the first phosphor layer fluorescent slurry on the aluminum nitride substrate: Printing the first phosphor layer fluorescent slurry on the fluorescent reflection surface of the aluminum nitride substrate by screen printing to obtain a first phosphor layer wet film;
[0047] (5) Pre-drying the wet film of the first phosphor layer: drying the wet film of the first phosphor layer in an oven, controlling the pre-drying temperature at 100-120° C., and keeping the temperature for 30-60 min to obtain a dry film of the first phosphor layer;
[0048] (6) Laminating and drying the remaining layers of fluorescent slurry: coating and drying the remaining layers of fluorescent slurry in sequence according to the methods of steps (4) and (5);
[0049] (7) Sintering to obtain a finished product: In an air atmosphere, the aluminum nitride substrate with an n-layer phosphor layer attached to the surface prepared in step (6) is sintered in a high-temperature sintering furnace, the peak sintering temperature is controlled at 750-850° C., and the temperature is kept at 30-90 minutes to obtain a wavelength conversion device.
[0050] The following examples more specifically describe the contents disclosed in the present application. These examples are intended for illustrative purposes only, since various modifications and changes within the scope of the contents disclosed in the present application will be apparent to those skilled in the art. Example 1
[0051] like Figure 1 As shown, this embodiment discloses a reflective wavelength conversion device, including a fluorescent layer 1 and a heat-conducting reflective layer 2 arranged below the fluorescent layer, wherein the fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles, and the fluorescent layer 1 includes three fluorescent powder layers, the first fluorescent powder layer 11 is close to the heat-conducting reflective layer 2, the outermost layer away from the heat-conducting reflective layer 2 is the third fluorescent powder layer 13, and the second fluorescent powder layer 12 is arranged between the first fluorescent powder layer 11 and the third fluorescent powder layer 13, and the fluorescent powder content in the first fluorescent powder layer 11 to the third fluorescent powder layer 13 increases layer by layer, and the scattering particle content decreases layer by layer. Specifically, in the first fluorescent powder layer 11, the mass ratio of the fluorescent powder to the glass powder is 0.2:1, and the mass ratio of the scattering particles to the glass powder is 0.8:1. The mass ratio of phosphor to glass powder in the second phosphor layer 12 is 0.8:1, and the mass ratio of scattering particles to glass powder is 0.5:1; the mass ratio of phosphor to glass powder in the third phosphor layer is 1.5:1, and the mass ratio of scattering particles to glass powder is 0.15:1. The thickness of the first phosphor layer 11, the second phosphor layer 12, and the third phosphor layer 13 are all about 30 μm. The thermal conductive reflective layer 2 includes a porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22, and an aluminum nitride layer 21 stacked in sequence, and the porous aluminum oxide layer 23 is arranged close to the fluorescent layer 1. Specifically, the thickness of the porous aluminum oxide layer 23 is about 60 μm, the thickness of the aluminum oxide-aluminum nitride transition layer 22 is about 10 μm, and the total thickness of the thermal conductive reflective layer 2 is 0.8 mm. The pore size of the pores of the porous aluminum oxide layer 23 is 100-400 nm.
[0052] Specifically, in this embodiment, the scattering particles are aluminum oxide with a particle size of 50-100 nm. In other embodiments, the scattering particles can also be one or a combination of titanium oxide, zirconium oxide, magnesium oxide, zinc oxide, and lithopone, and the particle size is 40-200 nm, which has a good scattering effect.
[0053] Specifically, in this embodiment, the glass powder is a Zn / B / Si / O system, with a particle size of 1-6 μm and a softening temperature of 500-700° C. In other embodiments, the glass powder may also be an Al / Zn / B / O system or a B / Si / O system.
[0054] The method for preparing the reflective wavelength conversion device described in this embodiment comprises the following steps:
[0055] (1) Oxidation treatment of the heat sink substrate: A 0.8 mm thick aluminum nitride substrate was placed in an oxygen atmosphere, the oxygen partial pressure was controlled to 0.08 MPa, the heat treatment temperature was 850°C, and the temperature was kept for 45 minutes to obtain an oxidized aluminum nitride substrate with a 60 μm thick porous aluminum oxide layer 23 on the surface and a 10 μm thick aluminum oxide-aluminum nitride transition layer 22 in the middle.
[0056] (2) Grinding and polishing the oxidized aluminum nitride substrate: One side of the oxidized aluminum nitride substrate is left as a fluorescent reflection surface without any treatment, and the remaining surface of the oxidized aluminum nitride substrate is ground and polished to expose the aluminum nitride layer 21.
[0057] (3) Preparing fluorescent slurry: prepare different layers of fluorescent slurry according to the proportions of the first fluorescent powder layer 11, the second fluorescent powder layer 12, and the third fluorescent powder layer 13: add glass powder, scattering particles and fluorescent powder into a mortar according to the proportions, add organic solvent (pinene alcohol), grind and stir for 30 minutes, and then stir under planetary vacuum for 10 minutes to evenly disperse and degas the components, thereby obtaining fluorescent slurry for the first fluorescent powder layer, fluorescent slurry for the second fluorescent powder layer, and fluorescent slurry for the third fluorescent powder layer.
[0058] (4) Laminating the first phosphor layer fluorescent slurry on the aluminum nitride substrate: The first phosphor layer fluorescent slurry is printed on the fluorescent reflective surface of the aluminum nitride substrate by screen printing to obtain a first phosphor layer wet film.
[0059] (5) Pre-drying the wet film of the first phosphor layer: Dry the wet film of the first phosphor layer in an oven, control the pre-drying temperature at 100-120° C., and keep it warm for 30-60 minutes to obtain a dry film of the first phosphor layer with a thickness of about 30 μm.
[0060] (6) Coating and drying the remaining layers of fluorescent slurry: coating the second fluorescent slurry on the first fluorescent powder layer dry film by referring to the method of step (4) and step (5), and drying to obtain the second fluorescent powder layer dry film; coating the third fluorescent slurry on the second fluorescent powder layer dry film by referring to the method of step (4) and step (5), and drying to obtain the third fluorescent powder layer dry film.
[0061] (7) Sintering to obtain a finished product: In an air atmosphere, the aluminum nitride substrate with three phosphor layers attached to the surface prepared in step (6) is sintered in a high-temperature sintering furnace, the peak sintering temperature is controlled at 750-850° C., and the temperature is kept at 30-90 minutes to obtain a wavelength conversion device. Example 2
[0062] like Figure 2As shown, this embodiment discloses a reflective wavelength conversion device, including a fluorescent layer 1 and a thermal conductive reflective layer 2 arranged below the fluorescent layer 1, wherein the fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles, and the fluorescent layer 1 includes 4 fluorescent powder layers, the first fluorescent powder layer 11 is close to the thermal conductive reflective layer 2, the outermost layer away from the thermal conductive reflective layer 2 is the fourth fluorescent powder layer 14, and the second fluorescent powder layer 12 and the third fluorescent powder layer 13 are arranged in sequence between the first fluorescent powder layer 11 and the fourth fluorescent powder layer 14; the fluorescent powder content in the first fluorescent powder layer 11 to the fourth fluorescent powder layer 14 increases layer by layer, and the scattering particle content decreases layer by layer. Specifically, in the first fluorescent powder layer 11, the mass ratio of the fluorescent powder to the glass powder is 0.2:1, and the mass ratio of the scattering particles to the glass powder is 0.8:1. In the second fluorescent powder layer 12, the mass ratio of the fluorescent powder to the glass powder is 0.6:1, and the mass ratio of the scattering particles to the glass powder is 0.6:1. The mass ratio of phosphor to glass powder in the third phosphor layer 13 is 0.8:1, and the mass ratio of scattering particles to glass powder is 0.5:1. The mass ratio of phosphor to glass powder in the fourth phosphor layer 14 is 1.5:1, and the mass ratio of scattering particles to glass powder is 0.15:1. The thicknesses of the first phosphor layer 11, the second phosphor layer 12, the third phosphor layer 13, and the fourth phosphor layer 14 are 30 μm, 15 μm, 15 μm, and 30 μm, respectively. The thermal conductive reflective layer 2 includes a porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22, and an aluminum nitride layer 21 stacked in sequence, and the porous aluminum oxide layer 23 is arranged close to the fluorescent layer 1. Specifically, the thickness of the porous aluminum oxide layer 23 is about 60 μm, the thickness of the aluminum oxide-aluminum nitride transition layer 22 is about 10 μm, and the total thickness of the thermal conductive reflective layer 2 is 0.8 mm. The pores of the porous alumina layer 23 have a pore size of 100-400 nm.
[0063] The difference between the present embodiment 2 and the embodiment 1 is only that the fluorescent layer 1 and the preparation method thereof are different. The fluorescent layer 1 of the present embodiment 2 has four layers of gradient-distributed fluorescent powder layers, while the fluorescent powder layers of the embodiment 1 have three layers of gradient-distributed fluorescent powder layers. The preparation method of the reflective wavelength conversion device of the present embodiment 2 is the same as that of the embodiment 1 except that the ratio and thickness of the fluorescent layer 1 are different and the coating and drying processes are different. The preparation method of the wavelength conversion device of the present embodiment can be adaptively adjusted according to the preparation method of the embodiment 1, and other similarities between the present embodiment 2 and the embodiment 1 are not repeated here. Example 3
[0064] like Figure 3As shown, this embodiment discloses a reflective wavelength conversion device, comprising a fluorescent layer 1 and a heat-conducting reflective layer 2 arranged below the fluorescent layer, wherein the fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles, and the fluorescent layer 1 comprises 5 fluorescent powder layers, the first fluorescent powder layer 11 is close to the heat-conducting reflective layer 2, the outermost layer away from the heat-conducting reflective layer 2 is the fifth fluorescent powder layer 14, and the second fluorescent powder layer 12, the third fluorescent powder layer 13 and the fourth fluorescent powder layer 14 are arranged in sequence between the first fluorescent powder layer 11 and the fifth fluorescent powder layer 15; the fluorescent powder content in the first fluorescent powder layer 11 to the fifth fluorescent powder layer 15 increases layer by layer, and the scattering particle content decreases layer by layer. Specifically, in the first fluorescent powder layer 11, the mass ratio of the fluorescent powder to the glass powder is 0.1:1, and the mass ratio of the scattering particles to the glass powder is 1:1. In the second fluorescent powder layer 12, the mass ratio of the fluorescent powder to the glass powder is 0.3:1, and the mass ratio of the scattering particles to the glass powder is 0.7:1. The mass ratio of phosphor to glass powder in the third phosphor layer 13 is 0.5:1, and the mass ratio of scattering particles to glass powder is 0.5:1. The mass ratio of phosphor to glass powder in the fourth phosphor layer 14 is 0.7:1, and the mass ratio of scattering particles to glass powder is 0.3:1. The mass ratio of phosphor to glass powder in the fifth phosphor layer 15 is 2:1, and the mass ratio of scattering particles to glass powder is 0.15:1. The thicknesses of the first phosphor layer 11, the second phosphor layer 12, the third phosphor layer 13, the fourth phosphor layer 14, and the fifth phosphor layer 15 are 20 μm, 10 μm, 15 μm, 20 μm, and 20 μm, respectively. The thermal conductive reflective layer 2 includes a porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22, and an aluminum nitride layer 21 stacked in sequence, and the porous aluminum oxide layer 23 is disposed close to the phosphor layer 1. Specifically, the thickness of the porous aluminum oxide layer is about 60 μm, the thickness of the aluminum oxide-aluminum nitride transition layer is about 10 μm, and the total thickness of the heat conductive reflective layer is 0.8 mm. The pores of the porous aluminum oxide layer 23 have a pore size of 100-400 nm.
[0065] The difference between the present embodiment 3 and the embodiment 1 is only that the fluorescent layer 1 and the preparation method thereof are different. The fluorescent layer 1 of the present embodiment 3 has 5 layers of gradient-distributed fluorescent powder layers, while the fluorescent powder layers of the embodiment 1 have 3 layers of gradient-distributed fluorescent powder layers. The preparation method of the reflective wavelength conversion device of the present embodiment 3 is the same as that of the embodiment 1 except that the ratio and thickness of the fluorescent layer 1 are different and the coating and drying processes are different. The preparation method of the wavelength conversion device of the present embodiment can be adaptively adjusted according to the preparation method of the embodiment 1, and other similarities between the present embodiment 3 and the embodiment 1 are not repeated here. Example 4
[0066] like Figure 4As shown, this embodiment discloses a reflective wavelength conversion device, including a fluorescent layer 1 and a thermally conductive reflective layer 2 arranged below the fluorescent layer 1, wherein the fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles, and the fluorescent layer 1 includes two fluorescent powder layers, the first fluorescent powder layer 11 is close to the thermally conductive reflective layer 2, and the second fluorescent powder layer 12 is far away from the thermally conductive reflective layer 2. Specifically, in the first fluorescent powder layer 11, the mass ratio of the fluorescent powder to the glass powder is 0.3:1, and the mass ratio of the scattering particles to the glass powder is 0.7:1. In the second fluorescent powder layer 12, the mass ratio of the fluorescent powder to the glass powder is 2:1, and the mass ratio of the scattering particles to the glass powder is 0.2:1. The first fluorescent powder layer 11 and the second fluorescent powder layer 12 are both 40μm. The thermally conductive reflective layer 2 includes a porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22 and an aluminum nitride layer 21 stacked in sequence, and the porous aluminum oxide layer 23 is arranged close to the fluorescent layer 1. Specifically, the thickness of the porous aluminum oxide layer is about 60 μm, the thickness of the aluminum oxide-aluminum nitride transition layer is about 10 μm, and the total thickness of the heat conductive reflective layer is 0.8 mm. The pores of the porous aluminum oxide layer 23 have a pore size of 100-400 nm.
[0067] The difference between the present embodiment 4 and the embodiment 1 is only that the fluorescent layer and the preparation method thereof are different. The fluorescent layer 1 of the present embodiment 4 has two layers of gradient-distributed fluorescent powder layers, while the fluorescent powder layers of the embodiment 1 have three layers of gradient-distributed fluorescent powder layers. The preparation method of the reflective wavelength conversion device of the present embodiment 4 is the same as that of the embodiment 1 except that the ratio and thickness of the fluorescent layer 1 are different and the coating and drying processes are different. The preparation method of the wavelength conversion device of the present embodiment can be adaptively adjusted according to the preparation method of the embodiment 1, and other similarities between the present embodiment 4 and the embodiment 1 are not repeated here. Example 5
[0068] like Figure 5As shown, this embodiment discloses a reflective wavelength conversion device, including a fluorescent layer 1 and a heat-conducting reflective layer 2 arranged below the fluorescent layer 1, wherein the fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles, and the fluorescent layer 1 includes three fluorescent powder layers, the first fluorescent powder layer 11 is close to the heat-conducting reflective layer 2, the outermost layer away from the heat-conducting reflective layer 2 is the third fluorescent powder layer 13, and the second fluorescent powder layer 12 is arranged between the first fluorescent powder layer 11 and the third fluorescent powder layer 13, and the fluorescent powder content in the first fluorescent powder layer 11 to the third fluorescent powder layer 13 increases layer by layer, and the scattering particle content decreases layer by layer. Specifically, in the first fluorescent powder layer 11, the mass ratio of the fluorescent powder to the glass powder is 0.2:1, and the mass ratio of the scattering particles to the glass powder is 0.8:1. The mass ratio of phosphor to glass powder in the second phosphor layer 12 is 0.8:1, and the mass ratio of scattering particles to glass powder is 0.5:1; the mass ratio of phosphor to glass powder in the third phosphor layer is 1.5:1, and the mass ratio of scattering particles to glass powder is 0.15:1. The thickness of the first phosphor layer 11, the second phosphor layer 12, and the third phosphor layer 13 are all about 30 μm. The thermal conductive reflective layer 2 includes a porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22, and an aluminum nitride layer 21 stacked in sequence, and the porous aluminum oxide layer 23 is arranged close to the fluorescent layer 1. Specifically, the thickness of the porous aluminum oxide layer 23 is about 50 μm, the thickness of the aluminum oxide-aluminum nitride transition layer 22 is about 15 μm, and the total thickness of the thermal conductive reflective layer 2 is 0.8 mm. The pore size of the pores of the porous aluminum oxide layer 23 is 100-400 nm.
[0069] The difference between this embodiment 5 and embodiment 1 is that the thickness of the porous aluminum oxide layer 23 and the aluminum oxide-aluminum nitride transition layer 22 is different from that of embodiment 1. The thickness of the porous aluminum oxide layer 23 and the aluminum oxide-aluminum nitride transition layer 22 can be adjusted by controlling the oxygen partial pressure, the sintering temperature and the insulation time. Specifically, the oxidation treatment of the heat sink substrate in this embodiment is as follows: a 0.8 mm thick aluminum nitride substrate is placed in an oxygen atmosphere, the oxygen partial pressure is controlled to be 0.06 MPa, the heat treatment temperature is 800°C, and the insulation time is 60 minutes to obtain an oxidized aluminum nitride substrate having a 50 μm thick porous aluminum oxide layer 23 on the surface and a 15 μm thick aluminum oxide-aluminum nitride transition layer 22 in the middle.
[0070] The rest of the structure and preparation process of Example 5 are the same as those of Example 1 and will not be described again here. Example 6
[0071] like Figure 6As shown, this embodiment discloses a reflective wavelength conversion device, including a fluorescent layer 1 and a heat-conducting reflective layer 2 arranged below the fluorescent layer 1, wherein the fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles, and the fluorescent layer 1 includes three fluorescent powder layers, the first fluorescent powder layer 11 is close to the heat-conducting reflective layer 2, the outermost layer away from the heat-conducting reflective layer 2 is the third fluorescent powder layer 13, and the second fluorescent powder layer 12 is arranged between the first fluorescent powder layer 11 and the third fluorescent powder layer 13, and the fluorescent powder content in the first fluorescent powder layer 11 to the third fluorescent powder layer 13 increases layer by layer, and the scattering particle content decreases layer by layer. Specifically, in the first fluorescent powder layer 11, the mass ratio of the fluorescent powder to the glass powder is 0.2:1, and the mass ratio of the scattering particles to the glass powder is 0.8:1. The mass ratio of phosphor to glass powder in the second phosphor layer 12 is 0.8:1, and the mass ratio of scattering particles to glass powder is 0.5:1; the mass ratio of phosphor to glass powder in the third phosphor layer is 1.5:1, and the mass ratio of scattering particles to glass powder is 0.15:1. The thickness of the first phosphor layer 11, the second phosphor layer 12, and the third phosphor layer 13 are all about 30 μm. The thermal conductive reflective layer 2 includes a porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22, and an aluminum nitride layer 21 stacked in sequence, and the porous aluminum oxide layer 23 is arranged close to the fluorescent layer 1. Specifically, the thickness of the porous aluminum oxide layer 23 is about 70 μm, the thickness of the aluminum oxide-aluminum nitride transition layer 22 is about 5 μm, and the total thickness of the thermal conductive reflective layer 2 is 0.8 mm. The pore size of the pores of the porous aluminum oxide layer 23 is 100-400 nm.
[0072] The difference between this embodiment 6 and embodiment 1 is that the thickness of the porous aluminum oxide layer 23 and the aluminum oxide-aluminum nitride transition layer 22 are different from those in embodiment 1. Specifically, the oxidation treatment of the heat sink substrate in this embodiment is as follows: a 0.8 mm thick aluminum nitride substrate is placed in an oxygen atmosphere, the oxygen partial pressure is controlled to be 0.1 MPa, the heat treatment temperature is 900°C, and the temperature is kept for 30 minutes to obtain an oxidized aluminum nitride substrate having a 70 μm thick porous aluminum oxide layer 23 on the surface and a 5 μm thick aluminum oxide-aluminum nitride transition layer 22 in the middle.
[0073] The rest of the structure and preparation process of Example 6 are the same as those of Example 1 and will not be described again here. Comparative Example 1
[0074] like Figure 7As shown, a reflective wavelength conversion device comprises a fluorescent layer 1 and a heat-conducting reflective layer 2 arranged below the fluorescent layer. The fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles. The fluorescent layer 1 comprises three fluorescent powder layers. The first fluorescent powder layer 11 is close to the heat-conducting reflective layer 2, and the outermost layer away from the heat-conducting reflective layer 2 is the third fluorescent powder layer 13. A second fluorescent powder layer 12 is arranged between the first fluorescent powder layer 11 and the third fluorescent powder layer 13. The content of fluorescent powder increases layer by layer and the content of scattering particles decreases layer by layer in the first fluorescent powder layer 11 to the third fluorescent powder layer 13. Specifically, in the first fluorescent powder layer 11, the mass ratio of fluorescent powder to glass powder is 0.2:1, and the mass ratio of scattering particles to glass powder is 0.8:1. In the second fluorescent powder layer 12, the mass ratio of fluorescent powder to glass powder is 0.8:1, and the mass ratio of scattering particles to glass powder is 0.5:1; in the third fluorescent powder layer, the mass ratio of fluorescent powder to glass powder is 1.5:1, and the mass ratio of scattering particles to glass powder is 0.15:1. The thickness of the first phosphor layer 11, the second phosphor layer 12 and the third phosphor layer 13 are all about 30 μm. The thermally conductive substrate is an aluminum nitride substrate.
[0075] The preparation process of the reflective wavelength conversion device is as follows:
[0076] (1) Preparing fluorescent slurry: Prepare different layers of fluorescent slurry according to the proportions of the first fluorescent powder layer 11, the second fluorescent powder layer 12, and the third fluorescent powder layer 13: Add glass powder, scattering particles and fluorescent powder into a mortar according to the proportions, add organic solvent (pinene alcohol), grind and stir for 30 minutes, and then stir under planetary vacuum for 10 minutes to evenly disperse and degas the components, thereby obtaining fluorescent slurry for the first fluorescent powder layer, fluorescent slurry for the second fluorescent powder layer, and fluorescent slurry for the third fluorescent powder layer.
[0077] (2) Coating the first phosphor layer fluorescent slurry on the aluminum nitride substrate: The first phosphor layer fluorescent slurry is printed on the surface of the aluminum nitride substrate with a thickness of 0.8 mm by using a screen printing process to obtain a first phosphor layer wet film.
[0078] (3) Pre-drying the wet film of the first phosphor layer: Dry the wet film of the first phosphor layer in an oven, control the pre-drying temperature at 100-120° C., and keep it warm for 30-60 minutes to obtain a dry film of the first phosphor layer with a thickness of about 30 μm.
[0079] (4) Coating and drying the remaining layers of fluorescent slurry: coating the second fluorescent slurry on the first fluorescent powder layer dry film by referring to the method of step (4) and step (5), and drying to obtain the second fluorescent powder layer dry film; coating the third fluorescent slurry on the second fluorescent powder layer dry film by referring to the method of step (4) and step (5), and drying to obtain the third fluorescent powder layer dry film.
[0080] (5) Sintering to obtain a finished product: In an air atmosphere, the aluminum nitride substrate with three phosphor layers attached to the surface prepared in step (4) is sintered in a high-temperature sintering furnace, the peak sintering temperature is controlled at 750-850° C., and the temperature is kept at 30-90 minutes to obtain a wavelength conversion device. Comparative Example 2
[0081] like Figure 8 As shown, this embodiment discloses a reflective wavelength conversion device, comprising a fluorescent layer 1 and a heat-conducting reflective layer 2 arranged below the fluorescent layer, wherein the fluorescent layer 1 is obtained by sintering fluorescent powder, glass powder and scattering particles, specifically, the mass ratio of the fluorescent powder to the glass powder in the fluorescent layer is 0.8:1, the mass ratio of the scattering particles to the glass powder is 0.5:1, and the thickness of the fluorescent layer is about 90 μm. The heat-conducting reflective layer 2 comprises a porous aluminum oxide layer 23, an aluminum oxide-aluminum nitride transition layer 22 and an aluminum nitride layer 21 stacked in sequence, and the porous aluminum oxide layer 23 is arranged close to the fluorescent layer 1. Specifically, the thickness of the porous aluminum oxide layer 23 is about 60 μm, the thickness of the aluminum oxide-aluminum nitride transition layer 22 is about 10 μm, and the total thickness of the heat-conducting reflective layer 2 is 0.8 mm. The pore size of the pores of the porous aluminum oxide layer 23 is 100-400 nm.
[0082] The preparation method of the reflective wavelength conversion device is as follows:
[0083] (1) Oxidation treatment of the heat sink substrate: A 0.8 mm thick aluminum nitride substrate was placed in an oxygen atmosphere, the oxygen partial pressure was controlled to 0.08 MPa, the heat treatment temperature was 850°C, and the temperature was kept for 45 minutes to obtain an oxidized aluminum nitride substrate with a 60 μm thick porous aluminum oxide layer 23 on the surface and a 10 μm thick aluminum oxide-aluminum nitride transition layer 22 in the middle.
[0084] (2) Grinding and polishing the oxidized aluminum nitride substrate: One side of the oxidized aluminum nitride substrate is left as a fluorescent reflection surface without any treatment, and the remaining surface of the oxidized aluminum nitride substrate is ground and polished to expose the aluminum nitride layer 21.
[0085] (3) Preparation of fluorescent slurry: Add glass powder, scattering particles and fluorescent powder into a mortar according to proportion, add organic solvent (pinene alcohol), grind and stir for 30 minutes, and then stir under planetary vacuum for 10 minutes to evenly disperse the components and remove bubbles to obtain fluorescent slurry.
[0086] (4) Coating the aluminum nitride substrate with fluorescent slurry: The fluorescent slurry is printed on the fluorescent reflective surface of the aluminum nitride substrate using a screen printing process to obtain a wet film of the fluorescent powder layer.
[0087] (5) Pre-drying the wet film of the phosphor layer: Dry the wet film of the phosphor layer in an oven, control the pre-drying temperature at 100-120°C, and keep it warm for 30-60 minutes to obtain a dry film of the phosphor layer with a thickness of about 90 μm.
[0088] (6) Sintering to obtain a finished product: In an air atmosphere, the aluminum nitride substrate with a phosphor layer attached to the surface prepared in step (5) is sintered in a high-temperature sintering furnace, the peak sintering temperature is controlled at 750-850° C., and the temperature is kept at 30-90 minutes to obtain a wavelength conversion device.
[0089] The reflective wavelength conversion devices of Examples 1 to 6 and Comparative Examples 1 and 2 were subjected to performance tests, and the test items, test methods or standards were as follows:
[0090] 1. Test of blue light power tolerance: adjust the blue light power to a lower range, then continuously increase the blue light power and observe the change in luminous flux. When the luminous flux stops increasing or even decreases, record the blue light power, which is the limit value of the blue light power tolerance of the reflective wavelength conversion device. The luminous flux corresponding to the limit blue light power is the limit luminous flux.
[0091] 2. Luminous flux test: Light up the light source and align the light outlet of the light source with the entrance of the integrating sphere so that the light completely enters the integrating sphere. Test the luminous flux of the reflective wavelength conversion device at the extreme blue light power and at the low blue light power of 30w.
[0092] 3. Aging cycle reliability test: Test the change of the luminous flux of the wavelength conversion device before and after aging under high-temperature and low-temperature cycles. When the luminous flux after aging drops to 90% of that before aging, it is the tolerable limit aging time. Calculate the number of cycles to evaluate its reliability. High and low temperature test environment: high temperature 85℃, low temperature -40℃. One cycle 2h. The test results are shown in Table 1.
[0093] Table 1
[0094] As can be seen from Table 1, the reflective wavelength conversion device prepared by the present invention has high tolerance to extreme blue light power, extreme light flux, and 30W low blue light power light flux, and has good reliability. Comparing Example 1 and Comparative Example 1, it can be seen that the thermal conductive reflective layer is not pre-oxidized under oxygen partial pressure, and the light flux of the prepared wavelength conversion device is low. Comparing Example 1 and Comparative Example 2, it can be seen that the fluorescent layer is not gradient treated, and it is easy to form an interface alone, the luminous effect of the fluorescent layer will be poor, and the reliability of the wavelength conversion device will also be worse.
[0095] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A reflective wavelength conversion device, characterized in that: The invention comprises a fluorescent layer and a heat-conducting reflective layer arranged below the fluorescent layer, wherein the fluorescent layer is obtained by sintering fluorescent powder, glass powder and scattering particles, wherein the fluorescent layer comprises n fluorescent powder layers, wherein the first fluorescent powder layer is close to the thermally conductive reflective layer, and the outermost layer far away from the thermally conductive reflective layer is the nth fluorescent powder layer, 2≤n≤5, and the fluorescent powder content in the first fluorescent powder layer to the nth fluorescent powder layer increases layer by layer, and the scattering particle content decreases layer by layer, and the heat-conducting reflective layer comprises a porous aluminum oxide layer, an aluminum oxide-aluminum nitride transition layer and an aluminum nitride layer stacked in sequence, and the porous aluminum oxide layer is arranged close to the fluorescent layer.
2. The reflective wavelength conversion device according to claim 1, characterized in that: The mass ratio of the fluorescent powder to the glass powder in the fluorescent layer is (0.1-2):1, and the mass ratio of the scattering particles to the glass powder is (0.1-1):
1.
3. The reflective wavelength conversion device according to claim 2, characterized in that: The mass ratio of the phosphor to the glass powder in the first phosphor layer of the phosphor layer is (0.1-0.3):1, and the mass ratio of the scattering particles to the glass powder is (0.7-1):1; the mass ratio of the phosphor to the glass powder in the nth phosphor layer of the phosphor layer is (1-2):1, and the mass ratio of the scattering particles to the glass powder is (0.1-0.2):
1.
4. The reflective wavelength conversion device according to claim 1, characterized in that: The scattering particles are one or a combination of aluminum oxide, titanium oxide, zirconium oxide, magnesium oxide, zinc oxide, and lithopone, and the particle size is 20-400 nm.
5. The reflective wavelength conversion device according to claim 1, characterized in that: The softening temperature of the glass powder is 500-700° C. The glass powder is of Zn / B / Si / O system, Al / Zn / B / O system or B / Si / O system, and has a particle size of 1-6 μm.
6. The reflective wavelength conversion device according to claim 1, characterized in that: The porous aluminum oxide layer and the aluminum oxide-aluminum nitride transition layer of the heat-conducting reflective layer are obtained by oxidizing aluminum nitride.
7. The reflective wavelength conversion device according to claim 1, wherein: The pores of the porous alumina layer have a pore size of 100-400 nm.
8. The reflective wavelength conversion device according to claim 1, characterized in that: The thickness of the porous aluminum oxide layer is 50-70 μm, and the thickness of the aluminum oxide-aluminum nitride transition layer is 5-15 μm.
9. The reflective wavelength conversion device according to any one of claims 1 to 8, characterized in that: The thickness of the fluorescent layer is 80-140 μm, and the thickness of the heat-conducting reflective layer is 0.5-1 mm.
10. The method for preparing the reflective wavelength conversion device according to any one of claims 1 to 9, characterized in that: The steps include: (1) Oxidation treatment of the heat sink substrate: The aluminum nitride substrate is placed in an oxygen atmosphere, the oxygen partial pressure is controlled to be 0.06-0.1 MPa, the heat treatment temperature is 800-900°C, and the temperature is kept for 30-60 minutes to obtain an oxidized aluminum nitride substrate having a porous aluminum oxide layer on the surface and an aluminum oxide-aluminum nitride transition layer in the middle; (2) grinding and polishing the oxidized aluminum nitride substrate: one side of the oxidized aluminum nitride substrate is not processed in any way and serves as a fluorescent reflection surface, and the remaining surface of the oxidized aluminum nitride substrate is ground and polished to expose the aluminum nitride layer; (3) preparing fluorescent slurry: preparing fluorescent slurries of different layers according to the ratio of different fluorescent powder layers: adding glass powder, scattering particles and fluorescent powder into a mortar according to the ratio, adding organic solvent, grinding and stirring, and then planetary vacuum stirring to evenly disperse and remove bubbles of each component, to obtain fluorescent slurries of the first fluorescent powder layer,,,,, and the nth fluorescent powder layer respectively; (4) Laminating the first phosphor layer fluorescent slurry on the aluminum nitride substrate: Printing the first phosphor layer fluorescent slurry on the fluorescent reflection surface of the aluminum nitride substrate by screen printing to obtain a first phosphor layer wet film; (5) Pre-drying the wet film of the first phosphor layer: drying the wet film of the first phosphor layer in an oven, controlling the pre-drying temperature at 100-120° C., and keeping the temperature for 30-60 min to obtain a dry film of the first phosphor layer; (6) Laminating and drying the remaining layers of fluorescent slurry: coating and drying the remaining layers of fluorescent slurry in sequence according to the methods of steps (4) and (5); (7) Sintering to obtain a finished product: In an air atmosphere, the aluminum nitride substrate with an n-layer phosphor layer attached to the surface prepared in step (6) is sintered in a high-temperature sintering furnace, the peak sintering temperature is controlled at 750-850° C., and the temperature is kept at 30-90 minutes to obtain a wavelength conversion device.
Citation Information
Patent Citations
Diffuse reflection material, diffuse reflection layer, wavelength conversion apparatus and light source system
CN105732118A
Reflection type wavelength conversion device and preparation method thereof
CN118752864A
Wavelength conversion device, light-emitting device and projection system
US20160004147A1
Wavelength conversion device, manufacturing method thereof, and related illumination device
WO2014194864A1
Wavelength conversion apparatus
WO2019196431A1